2022
DOI: 10.1088/0256-307x/39/3/038701
|View full text |Cite
|
Sign up to set email alerts
|

Fluorination Increases Hydrophobicity at the Macroscopic Level but not at the Microscopic Level

Abstract: Hydrophobic interactions have been studied before in detail based on hydrophobic polymers, such as polystyrene (PS). Because fluorinated materials have relatively low surface energy, they often show both oleophobicity and hydrophobicity at the macroscopic level. However, it remains unknown how fluorination of hydrophobic polymer influences hydrophobicity at the microscopic level. We synthesized PS and fluorine-substituted PS (FPS) by employing the reversible addition-fragmentation chain transfer polymerization… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…The improvement of hydrophobicity is due to the fact that the strong electronegative fluorine can easily form hydrogen bonds with water molecules, thus forming a moisture-proof protective layer. In addition, the polarity of the fluorine–carbon chain is very low, so it has a small surface tension, and it is difficult for water droplets to infiltrate the surface with a small surface tension, thereby achieving a hydrophobic effect . To more obviously observe the water barrier effect caused by the increase in hydrophobicity, we placed water droplets on the surface of PSK/undoped PTAA and PSK/343FP-doped PTAA films and recorded the decomposition rates in Figures S8 and S9.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The improvement of hydrophobicity is due to the fact that the strong electronegative fluorine can easily form hydrogen bonds with water molecules, thus forming a moisture-proof protective layer. In addition, the polarity of the fluorine–carbon chain is very low, so it has a small surface tension, and it is difficult for water droplets to infiltrate the surface with a small surface tension, thereby achieving a hydrophobic effect . To more obviously observe the water barrier effect caused by the increase in hydrophobicity, we placed water droplets on the surface of PSK/undoped PTAA and PSK/343FP-doped PTAA films and recorded the decomposition rates in Figures S8 and S9.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the polarity of the fluorine−carbon chain is very low, so it has a small surface tension, and it is difficult for water droplets to infiltrate the surface with a small surface tension, thereby achieving a hydrophobic effect. 32 To more obviously observe the water barrier effect caused by the increase in hydrophobicity, we placed water droplets on the surface of PSK/undoped PTAA and PSK/343FP-doped PTAA films and recorded the decomposition rates in Figures S8 and S9. The optimized film showed a lower degradation rate (36 min) compared to the pristine film (23 min).…”
Section: Resultsmentioning
confidence: 99%
“…AFM-based SMFS technology is helpful to establish the relationship between the chain structure, chain composition, and single-chain elasticity of synthetic polymers and the interaction between chains and their macromechanical properties and to understand the relationship between the structure and interaction of biological macromolecules and their biological functions. Figure b shows the typical force–extension curve of the unfolding CPS nanosphere in water (blue line). Driven by hydrophobic interactions, the CPS collapses into a compact nanospherical structure at the beginning of the force–extension curves . The long force plateau indicates that the unfolding nanosphere is under constant force before the collapsed nanosphere transforms into a fully extended chain.…”
Section: Resultsmentioning
confidence: 99%
“…Tang and co-authors reported that pH-sensitive carboxymethyl chitosan (CMCS) NPs with fluorinated surface modification could enhance cellular uptake and improve cytotoxicity in different tumor cells without the targeting recognition between host and ligands. Notably, the fluorinated decoration is different from the hydrophilic decorations mentioned above since it mainly exhibits hydrophobicity. However, unlike traditional hydrophobic decorations like polyalkane, the fluorinate decoration does not hate contacting with the water molecules. ,, Such unique amphiphilic (“amphiphobic” may be more appropriate) property might account for the excellent drug/gene delivery efficiency, but the underlying mechanism of the effect of the fluorinated decoration on the cellular delivery still remains elusive.…”
Section: Introductionmentioning
confidence: 99%